Triple-Negativity Identifies a Subgroup of Patients with Better Overall Survival in Essential Thrombocythemia - Marco Santoro; Vincenzo Accurso; Salvatrice Mancuso; Mariasanta Napolitano; Marta Mattana; Giorgia Vajana; Federica Russello; Sergio Siragusa (Hematology Reports, 2022)
Essential thrombocythemia, as defined by the WHO in 2016, is a Philadelphia-negative chronic myeloproliferative neoplasm showing a better prognosis than polycythemia vera and myelofibrosis. In a variable percentage, patients with essential thrombocythemia show none of the known driver-gene mutations that may occur on JAK2, CALR, and MPL genes. Such patients are classified as triple-negative and their clinical features and prognosis have not been described with precision yet. In this study, we evaluated some of the characteristics of this population by comparing them with those of patients with driver-gene mutated ET. Data from 266 consecutive essential thrombocythemia patients were analysed. Triple-negative patients had a significantly lower symptom load and a lower frequency of splenomegaly at diagnosis. The results show that the rate of thrombosis was equal in the two subgroups. Overall survival was slightly better in the triple-negative group of patients.